Investigation of social inequalities in quality of life and in health behaviors of residents in the city of limassol - Ellina, Panagiota; Middleton, Nicos; Lambrinou, Ekaterini; Kouta, Christiana (My University, 2021)
AIM: To investigate the size and extent of social inequalities in quality of life and health behaviors of residents in the city of Limassol, considering gender. MATERIAL AND METHOD: This is a descriptive correlational study. The desired size of the sample determined 450 residents in Limassol. Multi-stage sampling was performed on four levels. In order to ensure a satisfactory response rate, postal communication preceded. The data were collected door-to-door in the form of interviews. The following research tools were used: a questionnaire designed for the particular study, the International Physical Activity Measurement Questionnaire and the SF 36 Questionnaire quality of life. The statistical tests used are descriptive statistics, ANOVA statistical analysis, linear regression analysis, Chi-Square statistical analysis (X2) and predictive stepwise regression model. The significance level was set at p<0,05. RESULTS: Women seems to have lower values in both dimensions of the SF-36. Especially in mental dimension, differences between gender seems to be stronger, because men have higher mean values for all variables in the mental dimension. CONCLUSIONS: It seems that being men, young, highly educated, with high income, working full time and having a mild physical activity, there is significant higher level of quality life in relation to others. Gender factor influences the patterns of risk factors and this has a different impact on quality of life.
Keywords: Gender; Quality of Life; SF 36; Social Inequalities; Social Position